Portable XRF Technology to Quantify Pb in Bone In Vivo. (27th November 2014) - Specht, Aaron James; Weisskopf, Marc; Nie, Linda Huiling
Abstract : Lead is a ubiquitous toxicant. Bone lead has been established as an important biomarker for cumulative lead exposures and has been correlated with adverse health effects on many systems in the body. K-shell X-ray fluorescence (KXRF) is the standard method for measuring bone lead, but this approach has many difficulties that have limited the widespread use of this exposure assessment method. With recent advancements in X-ray fluorescence (XRF) technology, we have developed a portable system that can quantify lead in bone in vivo within 3 minutes. Our study investigated improvements to the system, four calibration methods, and system validation for in vivo measurements. Our main results show that the detection limit of the system is 2.9 ppm with 2 mm soft tissue thickness, the best calibration method for in vivo measurement is background subtraction, and there is strong correlation between KXRF and portable LXRF bone lead results. Our results indicate that the technology is ready to be used in large human population studies to investigate adverse health effects of lead exposure. The portability of the system and fast measurement time should allow for this technology to greatly advance the research on lead exposure and public/environmental health.